HAK KONSTITUSIONAL BERAGAMA DAN MAHKAMAH KONSTITUSI - Ahmad Fadlil Sumadi (Harmoni, 2012)
Constitution of the Republic of Indonesia Year 1945 is a written constitution that governs the relationship between the state and citizens. The philosophical outlook of the Indonesians towards their country: it is viewed as a gift from Allah as fruit of their struggle in building the state and achieving goals. Related to the matter of religion, figuratively, in the Preamble, there are (two) phrases, the “blessed in the grace of God Almighty” in the third paragraph and “Belief in God Almighty” in the latter part of the fourth paragraph. Fundamental provisions in the preamble, in particular the religious right, the articles of the 1945 Constitution elaborated by defining the constitutional rights and obligations. The Constitutional Court is designed constitutionally is to resolve constitutional issues in the change of the Constitution of the Republic of Indonesia Year 1945. The resolution of a constitutional dispute is by testing the constitutionality of the norms in the regulation of religious rights. There are several examples of the Constitutional Court decision relating to the constitutional rights of religion, namely Decision Number 12/PUU-V/2007 dated October 2, 2007 on Polygamy, Decision No. 140/PUU-VII/2009 dated 12 April 2010 regarding blasphemy, and Decision No. 46 / PUU-VIII/2010 dated February 17, 2012 Registration of Marriage.